Induction of in vitro flowering in the orchid Dendrobium Sonia 17. - Tee, Chong Siang; Mahmood, Maziah; Tan, Chon Seng (Springer Netherlands, 2008)
In this study, Dendrobium Sonia 17 plantlets were used to induce in vitro flowering. Infloresce nces were induced and rooting was inhibited in the half-strength Murashige and Skoog medium containing 20μ MN6-benzyladenine (BA). The medium with high P and low N contents was effective to in duce inflorescences while the medium with low P and high N contents was only effective to promote forming of shoots. In addition, the induced in vitro inflorescences were able to multiply and maintain without exhibiting a distinctive vegetative phase. Different morphologies of in vitro flowers such as incomplete flower structures, abnormal and unresupinated in vitro flowers were observed.